A Three-stage Multiple Criteria Decision Making Model Based on AHP-TOPSIS and AFS Concept Description. (September 2020) - Tao, Lili
Abstract: In this paper, we propose an integrated model to solve the multi-criteria decision making problem.Firstly, AHP method is applied to calculate the weight value of each attribute on all the alternatives; secondly, TOPSIS method is used to get the preference value based on the weights calculated in the first step; finally, AFS concept description algorithm is employed to give the semantic descriptions of performance characteristics for all the alternatives. Compared with other models, this model can not only consider the comprehensive preference value, but also consider the specific performance characteristic of the alternative, which makes the decision more scientific. The supplier selection problem is applied to explain the application ability of this model.